Temperature-dependent luminescence of europium-doped Ga₂O₃ ceramics - Kuat K. Kumarbekov; Askhat B. Kakimov; Zhakyp T. Karipbayev; Murat T. Kassymzhanov; Mikhail G. Brik; Chong-geng Ma; Michał Piasecki; Yana Suchikova; Meldra Kemere; Marina Konuhova (Optical Materials: X)
This study explores the synthesis and luminescent properties of europium-doped gallium oxide (Ga₂O₃:Eu) ceramics fabricated via electron beam-assisted synthesis (EBAS) at 1.4 MeV. The resulting Ga₂O₃:Eu ceramics exhibit a nanocrystalline structure with an average crystallite size of ∼30 nm, high crystallinity, and minimal lattice strain (<0.5 %). Luminescence analysis from 4 K to 300 K reveals both intrinsic and europium-induced emissions. While intrinsic Ga₂O₃ emission exhibits thermal quenching above 100 K, Eu³⁺-related emissions, notably the 611 nm red emission, show thermal stability, retaining ∼90 % of their intensity at 300 K. Additionally, a novel low-temperature emission peak at 1.74 eV, potentially associated with electron beam-induced defects, was detected, meriting further exploration. These findings indicate that Ga₂O₃:Eu ceramics synthesized via EBAS hold promise for optoelectronic, radiation detection, and high-temperature applications, given their rapid production and enhanced thermal stability.